Character Education Values in This Children's Short Story Collection Wants to Pee in Jakarta: Its Use in High School Learning - Azizah, Hilma Azmi; Purnani, Siwi Tri; Hasanah, Dina Fitria (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to describe the values of character education in the short story collection